Mechanical Properties and Microstructure of Alkali-Activated Cements with Granulated Blast Furnace Slag, Fly Ash and Desert Sand - Yunpeng Liu; Xihao Yang; Wendi Tian; Zhenbo Fu; Yimeng Zhao; Binghan Li; Shiji Li; Da Xu; Shige Yu; Zhiyu Yao; Tian Zhao; Xinfeng Ouyang; et al. (Buildings)
In this study, desert sand was used as supplementary materials in alkali-activated cements (AAC) with granulated blast furnace slag (GBFS) and fly ash (FA). For the first time, a systematic investigation was conducted on the effects of various treatment methods and contents of desert sand on the strength and microstructure of AAC. This study also analyzed the X-ray diffractometer (XRD), Scanning Electron Microscopy-Energy Dispersive X-ray Microanalysis (SEM-EDX), Mercury Intrusion Porosimetry (MIP), pH values, and Fourier-transform infrared spectroscopy (FT-IR) properties of AAC pastes containing differently treated desert sand to uncover the mechanisms by which these treatments and dosages influence mechanical properties of AAC. Untreated desert sand (DS), temperature-treated desert sand (DS-T), and ground desert sand for two different durations (20 mins and 30 mins) all exhibited some pozzolanic activity but primarily acted as fillers in the AAC pastes. Among the samples, DS-T demonstrated the highest pozzolanic activity, though it was still less than that of fly ash (FA). The optimal dosage for the modified desert sands was determined to be 10%. However, The optimal dosage of different modified desert sands is 10%. The flexural strength of DS-G30-10 reaches 6.62 MPa and the compressive strength reaches 72.3 MPa, showing the best comprehensive mechanical properties.